ANALISIS PERAN AKUNTANSI KEPERILAKUAN DALAM MENGHADAPI KINERJA ORGANISASI DI PT INDOFOOD - M Rapi Saputra; Ikhdan Fatih Hanif; M. Tio Riyando; Ratih Kusumastuti (Journal of Student Research, 2023)
This purpose of this study is to analyze the role of behavioral accounting in addressing organizational performance at PT Indofood, a leading food and beverage company in Indonesia. Behavioral accounting focuses on understanding and influencing the behavior of individuals within an organization to improve performance. The study explores the application of behavioral accounting techniques and their impact on the overall performance of PT Indofood. By examining the relationship between behavior and organizational outcomes, this analysis provides insights into the effectiveness of behavioral accounting in enhancing performance and achieving organizational goals. The findings highlight the importance of integrating behavioral accounting practices in PT Indofood's management strategies to foster a positive work environment, enhance employee motivation, and ultimately improve organizational performance